SGLT2 inhibitors and incretin agents: Associations with alanine aminotransferase activity in type 2 diabetes - Bajaj, H.S.; Brown, R.E.; Bhullar, L.; Sohi, N.; Kalra, S.; Aronson, R. (Diabetes & metabolism, 2018)
•What is current knowledge?∘Non-alcoholic fatty liver disease (NAFLD) associated with type 2 diabetes (T2D) is a growing epidemic.∘Thiazolidinediones are the only class of diabetes therapies with proven beneficial liver effects.∘The effect of newer diabetes therapies on markers of NAFLD is uncertain.•What is new here?∘SGLT2 inhibitors were associated with significantly greater reductions in ALT compared to incretin therapies.∘This association for SGLT2 inhibitors, but not for incretin medications, was independent of weight and A1c change. A similar association between SGLT2 inhibitors and ALT change persisted in a propensity score weighted analysis that balanced baseline characteristics between treatment groups.∘A significant dose-response relationship was observed for ALT reduction with SGLT2 inhibitors at higher baseline ALT levels. The impact of new classes of glucose lowering medications on markers of non-alcoholic fatty liver disease (NAFLD) associated with type 2 diabetes (T2D) have been inconsistent in their magnitude and independence. This large retrospective study investigates changes in alanine aminotransferase (ALT) levels among subjects initiated on newer classes of T2D medications in comparison to a reference control group. We studied people with T2D from a large Canadian diabetes register, who had canagliflozin, dapagliflozin, liraglutide, sitagliptin or no further treatment added to their diabetes treatments. Stepwise multiple regression was used to determine the association of A1c and weight change on ALT. Propensity score weighting was used to balance baseline characteristics between treatment groups. A total of 3667 subjects met study criteria. ALT levels (mean follow-up 4.8 months) were lower after treatment with sodium glucose co-transporter 2 (SGLT2) inhibitors, canagliflozin (−4.3U/L, P<0.01) and dapagliflozin (−3.5U/L, P<0.01), compared to incretin agents, liraglutide (−2.1U/L, P<0.01) and sitagliptin (−1.8U/L, P<0.01), each greater than the control group. Only the SGLT2 inhibitor treatment groups maintained a significant ALT reduction vs. control following multivariable adjustment and propensity score weighting. Greater ALT reductions were seen with higher baseline ALT for both the SGLT2 inhibitor treatment groups. SGLT2 inhibitors canagliflozin and dapagliflozin resulted in a weight and A1c-independent reduction of ALT levels compared to incretin agents, with a dose-response observed at higher baseline ALT levels. Further studies investigating the differential effects of these drug classes on NAFLD, and insulin/glucagon levels as potential mechanism explaining these differences, should be performed.